“Cura gay" religiosa: análises a partir dos discursos produzidos pela literatura e as experiências de lésbicas, gays e bissexuais no Norte do Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
In Brazil in the 19th and 20th centuries, the discourse of psi sciences regarding gender and sexuality introduced into society the idea that expressions, gender identities and sexual orientations divergent from cis-heteronormativity would be subject to “cure” and “transformation”. The theme of this dissertation falls within a broad and complex field in which Sexuality, Religion and Psychology are intertwined. In the first study, we describe the path taken by this discourse, as well as the appropriation and use of part of it by Christian politicians and religious people, considering its plural properties as a social phenomenon, through the contributions of Foucauldian Discourse Analysis. In the second study, with a qualitative, descriptive-exploratory approach, we sought to understand the different outcomes and emerging effects in the experiences narrated by eight young people self-identified as lesbian, gay or bisexual, based on inspirations arising from the assumptions of Michel Foucault (2004, 2014) on the device of sexuality and subjectivation to discuss the results. Throughout the analyses, we highlighted the importance of Psychology in understanding the contemporary consequences of a pathologizing discourse produced precisely by the psi sciences. It was noticed that there is the maintenance of prejudiced and annihilating perspectives of lesbian, gay and bisexual existences, which the evangelical Pentecostal and neo-Pentecostal churches studied here promote and share. A rigid structure of surveillance, control and punishment that, through technologies and specific power relations, crosses bodies, subjectivizes subjects and produces erasure and violence. Thus, having lived “healing” experiences generated negative effects on the mental health of the collaborators in this study, causing damage to their self-concept, their emotions and future perspectives, and causing intense suffering - capable of influencing ideations and attempts of suicide. Finally, it is believed that it is possible to articulate interventions that are more appropriate to the reality and context experienced by them, and mainly, helping to promote mental health as an ethical and political care device.
Keywords: Programas de reorientação sexual; Orientação sexual; Homossexualidade; CIENCIAS HUMANAS; Terapias de Reorientação Sexual; Terapias de Conversão Religiosa; “Cura” Gay; Orientação Sexual; Psicologia